A Constructive Framework for Colour Vision Deficiency (CVD) in Digital Photography - Muhammad Azri Abdul Rahman; Nadzri Mohd Sharif; Liza Marziana Mohamad Noh; Moer Hasmadi Meor Hamzah; Fahmi Samsudin (Environment-Behaviour Proceedings Journal, 2025)
Studies show that around 8% of men and about 0.5% of women globally are affected by color blindness (Nathans et al., 1993; Neitz & Neitz, 2011), making the appreciation of photography challenging. Further research is required to explore the visual difficulties that color vision deficiency (CVD) photographers face. This study evaluates the visual skills of CVD photographers, explicitly focusing on the categories of Protanopia, Tritanopia, and Deuteranopia. It employs the HSx-Based Method, Contour Adjustment, Interpretation Process, and Perception Learning. After preliminary testing, experimental testing was conducted with control questions and minimal coaching. The Chi-square Test of Homogeneity classifies CVD and compares it to normal vision. Spearman’s Rho Correlation Test confirms that all CVD categories are "photosafe," providing valuable software and product development insights.